2001
DOI: 10.1002/mrd.1058
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic production from in vivo‐derived embryos: Effect on calf birth weight and sex ratio

Abstract: We examined transgenic-cattle production by DNA microinjection into 1-, 2-, and 4-cell embryos, analyzing the impact on calf size and subsequent viability. Embryos were either collected at an abattoir by flushing oviducts from superovulated and artificially inseminated cows (in vivo-derived) or obtained by in vitro maturation and in vitro fertilization of oocytes aspirated from excised ovaries (in vitro-derived). A human serum albumin (hSA) milk-expression DNA construct was microinjected, either in one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 58 publications
2
9
1
Order By: Relevance
“…Corresponding results for our previous studies were 44 and 32.2% (Duszewska et al, 2000;Rosochacki et al, 2001). The greater negative effect on embryo development in the present study may be due to the increase in microinjected DNA concentration (3 ng in our previous study vs 5 ng in this one), an observation that was also shown by Behboodi et al (2001). It should be pointed out, that the development of compacted morulae and blastocysts from 48 h cleaved embryos was very similar, being 48% in both groups.…”
Section: The Influence Of Gfp Construct Injection On the Development supporting
confidence: 70%
See 2 more Smart Citations
“…Corresponding results for our previous studies were 44 and 32.2% (Duszewska et al, 2000;Rosochacki et al, 2001). The greater negative effect on embryo development in the present study may be due to the increase in microinjected DNA concentration (3 ng in our previous study vs 5 ng in this one), an observation that was also shown by Behboodi et al (2001). It should be pointed out, that the development of compacted morulae and blastocysts from 48 h cleaved embryos was very similar, being 48% in both groups.…”
Section: The Influence Of Gfp Construct Injection On the Development supporting
confidence: 70%
“…A higher percentage of morulae and blastocysts was obtained by Wang et al (2001) but they also obtained a higher percentage of viable zygotes after injection (83%). The yield of morulae/blastocysts resulting from 1-cell in vivo derived embryos that had survived microinjection could have been even 50% higher than from equivalent in vitro-derived embryos (Krimpenfort et al, 1991;Behboodi et al, 1993;Behboodi et al, 2001). In our work we used only in vitro derived oocytes.…”
Section: The Influence Of Gfp Construct Injection On the Development mentioning
confidence: 96%
See 1 more Smart Citation
“…The results of the present study support this opinion in that, after microinjection, development to the blastocyst stage was only 10.4% compared with 39.9% for non-injected embryos (Table 1). This result is comparable with other studies in which the effi ciency of embryo development to the blastocyst stage ranged between 6 and 14% (Eyestone, 1999;Behboodi et al, 2001). In our experiment, the negative effect of transgene introduction occurred in the fi rst cell cycle because the microinjected embryos developed better (61.1%) from cleavage to the blastocyst stage than the control embryos (48.6%).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, this technique has stimulated interest in developing transgenic cattle, resulting in production of several transgenic cloned cattle. Initially, transgenesis in cattle was carried out by microinjecting DNA into pronuclear stage oocytes [1], as in rabbits, sheep and pigs [10]. After examining somatic cell nuclear transfer (SCNT) as a better approach to achieve transgenesis in cattle [21], donor cells containing target genes were reprogrammed in enucleated oocytes and produced transgenic calves [3,17,23].…”
mentioning
confidence: 99%